2009
DOI: 10.1534/genetics.108.098160
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Desirable Genetic Characteristics From an Inferior Into a Superior Population Using Genomic Selection

Abstract: Resistance to specific diseases may be improved by crossing a recipient line with a donor line (a distantly related strain) that is characterized by the desirable trait. However, considerable losses in the total merit index are expected when crossing recipient and donor lines. Repeated backcrossing with the recipient line will improve total merit index, but usually at the expense of the newly introgressed disease resistance, especially if this is due to polygenic effects rather than to a known single major QTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…This minimizes the bias of marker effects and is allows capturing small effects. Odegard et al (2009) showed that GS could be efficient in introgressing a polygenic trait from an inferior to a superior population by backcrossing. As our pseudo-backcross used E. guineensis individuals from elite families, this is a relevant starting point to introgress the fatty acid profile of E. oleifera into breeding populations of E. guineeenis.…”
Section: Resultsmentioning
confidence: 99%
“…This minimizes the bias of marker effects and is allows capturing small effects. Odegard et al (2009) showed that GS could be efficient in introgressing a polygenic trait from an inferior to a superior population by backcrossing. As our pseudo-backcross used E. guineensis individuals from elite families, this is a relevant starting point to introgress the fatty acid profile of E. oleifera into breeding populations of E. guineeenis.…”
Section: Resultsmentioning
confidence: 99%
“…The loss in genetic diversity can eventually lead to decreased genetic variance for the trait of interest and lower gain from selection (Robertson, 1960). In this case, a strategy which introgresses unrelated germplasm could be employed jointly with GS (Odegard et al, 2009;Bernardo, 2009). Another strategy would be a selection criterion that weights the low-frequency favorable alleles more heavily to avoid losing them.…”
Section: Breeding Implicationsmentioning
confidence: 99%
“…In aquaculture species, Odegard et al (2009b) demonstrated through computer simulation that GS is able to produce backcross lines that perform similarly or better than purebred lines within 3-5 generations. GS could be used to help to improve the genetic merit of polled cattle by shortening the generation interval and achieving a faster genetic progress compared to selection based on EBV estimation by BLUP.…”
Section: Introductionmentioning
confidence: 99%